Study on Natural Diatomite as an Adsorbent for Uranyl (VI) ions, Using Spectrophotometric Method - Issa, Ragiab A. M.; Hana B. AlHanash; Mona M. Abdulsalam; Amar A. Tekalli; Laila K. Ben Hamed; Suha A. Ben Omran (Journal of Pure & Applied Sciences, 2024)
This work is based on the investigation of uranyl (VI) ion adsorption onto natural diatomite using batch sorption method under different parameters such as pH, initial ion concentration, adsorbent amount and effect of sulfate ion as a foreign ion. 8-hydroxyquinoline is used as a chromogen forming a pale-yellow complex with  ions in chloroform, the absorbance was measured spectrophotometrically at λmax 460 nm, obtaining a linear calibration curve with R2=0.998, LOD=3.03 mg/L and LOQ=9.21 mg/L. Prior to the implementation of the batch experiment, the morphology and composition of diatomite was confirmed using XRF (Bruker S8 Tiger), XRD (Bruker D5005), FTIR (Bruker Vector 22), and SEM (JEOL JSM-5610 LV) techniques. From spectrophotometric analysis, the results showed that the maximum uranyl ion adsorption distribution coefficient reached at the initial concentration of 50ppm, pH 4.5, contact time 5hrs and adsorption dosage of 2 g/L. There was no significant effect of sulfate ion on the adsorption affinity. Adsorption isotherm was studied by Langmuir which was favourable model fitting with R2=0.996 and maximum adsorption capacity of 16mg/g, and separation factor RL = 0.0122. Freundlich isotherm model also applied for the same data and give a very straight line with R2= 1.00 and maximum adsorption capacity of 200 mg/g. Temkin model was less fit and gave a negative isotherm curve with R2= 0.78, KT= 0.9405 L/g, bT= 24.724 J/mol. Langmuir and Freundlich isotherms gave exothermic adsorption while Temkin gave an endothermic one.